On Some Aspects of Generalized Extended Yule Distribution: Properties and Applications - C. Satheesh Kumar; S. Harisankar (Journal of Advances in Applied & Computational Mathematics, 2020)
Martinez-Rodriguez (Comp. Statist. Dat. Anal., 2011) studied an extended version of the Yule distribution, namely “the extended Yule distribution (EYD)” which they obtained as a mixture of geometric distribution and generalized beta distribution. Through the present paper, we propose a generalized version of the EYD and named it “the generalized extended Yule distribution (GEYD)”. Several statistical properties of the distribution are obtained, including probability generating function (p.g.f), moments, recursion formulae etc. The maximum likelihood estimation of the parameters of the GEYD is discussed and fitted to two real-life data sets for illustrating its usefulness compared to the existing models. Further, the generalized likelihood ratio test procedure is considered for testing the significance of the parameters of the GEYD.